Determinants of Chinese Language Learning Demand: Evidence from North Central Vietnam - Nguyen Ngoc Anh; Bui Thi Van Nga (Acta Pedagogia Asiana, 2026)
: In the context of increasing economic integration, Chinese language proficiency has become an important asset for workforce competitiveness in Vietnam. This study investigates the factors influencing the demand for learning Chinese in the North Central region of Vietnam. Based on the theoretical foundations of foreign language learning motivation, the Theory of Planned Behavior, and Self-Determination Theory, a research model was developed and empirically tested using survey data from 489 respondents aged 15–35. The results of the SEM analysis indicate that the model achieves a good fit (χ²/df = 1.70, CFI = 0.967, TLI = 0.959, RMSEA = 0.054). Among the examined factors, employment opportunities (β = 0.537, p < 0.001) and information technology (β = 0.486, p < 0.001) have significant positive effects on learning demand, with employment opportunities exerting the strongest influence. In contrast, learning attitude and gender differences are not statistically significant (p > 0.05). These findings highlight the dominant role of practical and contextual factors over individual psychological traits in shaping language learning demand. The study contributes to the literature by providing empirical evidence from a less-explored regional context and offers practical implications for aligning language training programs with labor market needs and enhancing technology-supported learning environments.